ПАЦИЕНТ С ТРОМБОЭМБОЛИЕЙ ЛЁГОЧНОЙ АРТЕРИИ НА ПРИЁМЕ У ТЕРАПЕВТА - А. Л. Вёрткин; А. М. Грицанчук (SINAPS LLC, 2014)
Pulmonary embolism (PE) is the most frequent unrecognized cause of death of hospitalized patients. Mortality is about 30 %, which determines the relevance of the topic. Accurate statistics regarding the prevalence of PE in Russia does not exist. The exact number of nonfatal asymptomic PE is unknown. In most cases PE is a complication of deep venous thrombosis of the lower extremities and occurs not only in patients of cardiological profile. The article considers the ways of drug therapy and clinical examples.